Data from: Consequences of divergent temperature optima in a host-parasite system ... - Franke, Frederik; Raifarth, Nadja; Kurtz, Joachim; Scharsack, Jörn Peter (Dryad, 2019)
It was suggested that parasite infections become more severe with rising temperature, as expected during global warming. In ectothermic systems, the growth of a parasite and therefore its reproductive capacity is expected to increase with temperature. However, the outcome of the interaction depends on the temperature optima of both host and parasite. Here we used experimental infections of three-spined stickleback fish (Gasterosteus aculeatus) with its specific tapeworm parasite Schistocephalus solidus to investigate in detail the temperature optima for both host and parasite. We analyzed the fitness consequences thereof, focusing on growth and immunity of the host, and growth and offspring production of the parasite as fitness correlates. We checked for potential differences among populations, using the offspring of hosts and parasites derived from four study sites in Iceland, Germany and Spain that differ in average annual temperature ranging between 4.8 °C and 18.4 °C. We found differences in temperature ... : Data_Exp_4_Temperature_for_DryadExel file containing data of individual sticklebacks and parasites investigated in the present study. Corresponding columns indicate treatment, origin and tank of each individual. ...